Mga Talinghaya sa Laylayan - Morales-Nuncio, Elizabeth (Quezon City, 2005)
A collection of short stories that reflects the intricacies and experiences of marginalized communities in Philippine society, showcasing Filipino culture and traditions.
Keywords: Philippine poetry (Filipino)